2006
DOI: 10.7592/mt2006.34.kummel
|View full text |Cite
|
Sign up to set email alerts
|

Eesti etnofarmakognoosia elujõust kummelite näitel

Abstract: Teesid: Uute ravimtaimede avastamisel ja ammu tuntud droogide kasutusalade laiendamisel on etnofarmakognoosia farmaatsiateaduse igati tunnustatud ja nüüdisaegne suund. Käesolevas artiklis analüüsitakse eesti etnofarmakognoosia elujõulisust kummelite kui populaarseimate ravimtaimede näitel. Rahvameditsiinilise andmestiku läbitöötamine on võimaldanud siinkirjutajatel püstitada hüpoteesid, mille kohaselt võiks lõhnava kummeli ja teekummeli toimeid pidada samaväärseteks ning kasutada lõhnava kummeli ürti teekummel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…At the same time, the composition of the essential oil of Chamomilla suaveolens has been the subject of rather limited phytochemical investigations [9,[24][25][26][27][28][29][30][31][32][33], realized basically in the former USSR (Russia, Estonia, and Lithuania). The main biologically active compounds in the oils of Chamomilla recutita and C. suaveolens were found to be (E)-farnesene, (Z)-and (E)-en-yne-dicycloether, and farnesole [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the composition of the essential oil of Chamomilla suaveolens has been the subject of rather limited phytochemical investigations [9,[24][25][26][27][28][29][30][31][32][33], realized basically in the former USSR (Russia, Estonia, and Lithuania). The main biologically active compounds in the oils of Chamomilla recutita and C. suaveolens were found to be (E)-farnesene, (Z)-and (E)-en-yne-dicycloether, and farnesole [3].…”
mentioning
confidence: 99%
“…The concept that plants can be classified also on the basis of their chemical constituents is not new [1,2]. According to an earlier study [3], the most popular medicinal plant in Estonia during the 20th century was Chamomilla recutita (L.) Rauschert (= Matricaria recutita L.), which was also very widely used in the Soviet Union, Russia, Germany, etc. In several publications (an overview in [3]) it is observed that the chemical composition of the essential oil of Chamomilla recutita is rather similar to that of Chamomilla suaveolens (Pursh) Rydb.…”
mentioning
confidence: 99%